The Story of the Spar: An Oral History of the Hazel Pearl - Elliott, Heather; Barrett, Terra; Hannon, Sarah; Jarvis, Dale; Philpott, Michael. (2016)
The Story of the Spar: An Oral History of the Hazel Pearl. Booklet based on memories of the Hazel Pearl shipwreck and the story of the spar which was retrieved from the wreckage. Interviews and photographs completed during June 2015, and July 2016. Oral history interviews by Terra Barrett and Dale Jarvis. Research by Terra Barrett and Sarah Hannon. Research and editing by Heather Elliott. Spar drawing by Michael Philpott.